1989
DOI: 10.1002/ijc.2910430424
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptors, androgen‐dependent proliferation, and 5α‐reductase activity of small‐cell lung cancer cell lines

Abstract: We investigated the influence of testosterone on binding to established small-cell lung cancer (SCLC) cell lines and were able to show specific high-affinity and low-capacity binding sites in some cell lines with a typical receptor size, using sucrose density gradient centrifugation. In addition, we demonstrated marked growth stimulation with testosterone and dehydrotestosterone using different androgen-receptor-positive small-cell lung cancer cell lines. This growth stimulation could be counteracted by the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…Testosterone stimulates growth of small-cell lung cancer cell lines, an effect inhibited by AR antagonists (48). Alternatively, estrogenic mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone stimulates growth of small-cell lung cancer cell lines, an effect inhibited by AR antagonists (48). Alternatively, estrogenic mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The androgen receptor (AR) is present in normal and malignant lung tissue, and testosterone alters expression of genes regulating metabolism and apoptosis in malignant cells (45). Small-cell lung cancer cell lines are stimulated by testosterone, an effect blocked by AR antagonists (14). However, smoking can increase testosterone (15), suggesting the possibility of confounding.…”
Section: Discussionmentioning
confidence: 99%
“…We also recently reported an association between endogenous testosterone levels and lung cancer mortality in this cohort, although we lacked sufficient cases to conduct multivariate analyses after exclusion of smokers (13). Testosterone stimulates proliferation of smallcell lung cancer cell lines (14), but smoking can also increase testosterone (15). Whether this association would be maintained in analyses of incident lung cancer, rather than mortality alone (providing sufficient cases to allow exclusion of current smokers), is unclear.…”
Section: Introductionmentioning
confidence: 89%
“…Maasberg et al (1989) found that 8/13 cell lines had androgen receptors. The application of testosterone resulted in a 3-fold increase of cell proliferation in the cloning assay, whereas estrogen had no influence on tumour growth.…”
Section: Sclcmentioning
confidence: 99%